2014
DOI: 10.1371/journal.pone.0087312
|View full text |Cite
|
Sign up to set email alerts
|

Role of Alkyl Hydroperoxide Reductase (AhpC) in the Biofilm Formation of Campylobacter jejuni

Abstract: Biofilm formation of Campylobacter jejuni, a major cause of human gastroenteritis, contributes to the survival of this pathogenic bacterium in different environmental niches; however, molecular mechanisms for its biofilm formation have not been fully understood yet. In this study, the role of oxidative stress resistance in biofilm formation was investigated using mutants defective in catalase (KatA), superoxide dismutase (SodB), and alkyl hydroperoxide reductase (AhpC). Biofilm formation was substantially incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
88
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 56 publications
3
88
2
1
Order By: Relevance
“…Since a fur mutant constitutively expresses iron acquisition systems (Miller et al, 2009;van Vliet et al, 2002), this further complicates interpretation of transcriptomic and proteomic characterization of PerR regulation in C. jejuni. Inactivation of perR results in reduced colonization in chickens, suggesting a role of oxidative stress regulation in intestinal colonization (Palyada et al, 2009), although the reduced motility of the perR mutant reported in this study makes it difficult to distinguish the roles of motility and PerR on colonization.…”
Section: Introductionmentioning
confidence: 61%
See 4 more Smart Citations
“…Since a fur mutant constitutively expresses iron acquisition systems (Miller et al, 2009;van Vliet et al, 2002), this further complicates interpretation of transcriptomic and proteomic characterization of PerR regulation in C. jejuni. Inactivation of perR results in reduced colonization in chickens, suggesting a role of oxidative stress regulation in intestinal colonization (Palyada et al, 2009), although the reduced motility of the perR mutant reported in this study makes it difficult to distinguish the roles of motility and PerR on colonization.…”
Section: Introductionmentioning
confidence: 61%
“…Exposure of C. jejuni perR mutants to hydrogen peroxide on discs revealed that the level of peroxide resistance was considerably higher than previously reported, where 3 % hydrogen peroxide was used (Baillon et al, 1999;Flint & Stintzi, 2015;Palyada et al, 2009;van Vliet et al, 1999). Wild-type C. jejuni were sensitive to 5 % H 2 O 2 (Fig.…”
mentioning
confidence: 64%
See 3 more Smart Citations